Design of Retarding Basin as an Effort to Reduce Flood - Syafiatun Siregar; Harun Sitompul; Kinanti Wijaya; Ahmad Andi Solahuddin; Nurmaidah Nurmaidah (Jurnal Penelitian Pendidikan IPA, 2023)
The retarding basin functions as a body of water that is useful for temporarily storing water, namely by giving the opportunity for rainwater to seep into the ground. The concept of the retarding basin is to accommodate the volume of rainwater when the maximum discharge occurs. Medan Johor sub-district is part of 21 sub-districts in Medan City, which is located in the south of the city. Topographically, Medan Johor District has several basin areas that cause the water flow to be concentrated. Another problem is that the drainage channel in the Medan Johor Subdistrict is not functioning properly due to sedimentation from the garbage. When the rainy season arrives, Medan Johor District often experiences flooding. The impact of floods resulted in damage to public facilities and infrastructure, disruption of public services, and the emergence of social impacts in the community. The purpose of this study was to design aÂ retarding basin that serves to hold stagnant water temporarily. The water reservoir will then be channeled to the nearest sewer or river. Based on theoretical studies and analysis based on primary and secondary data, it is necessary to design a retarding basin in the Medan Johor District area to reduce flooding. From the results of the research conducted, it is necessary to design 3 (three) retarding basins in the Medan Johor area.